2022
DOI: 10.1111/oik.09213
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in root traits and root‐associated fungal community composition in a heteroblastic epiphytic bromeliad

Abstract: Heteroblastic variations among leaf traits is a well‐known process, especially in bromeliad species that show abrupt changes, but little effort was directed to test whether comparable ontogenetic variation occurs among root traits and their fungal partners. Usually considered for their mechanical role, roots of bromeliads may also play a role in resource use that we expect to differ between ontogenetic stages, namely nutrient pulse‐supplied atmospherics (young stage) and continuously‐supplied tanks (later stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…In contrast, Merino‐Martín and collaborators (2023) only observed differences in fungal, but not bacterial communities, between rhizosphere and bulk soil along an elevation gradient. This rhizosphere effect is also partly related to variation in inter‐ (Mafa‐Attoye et al 2023, Merino‐Martín et al 2023) and intraspecific (Gagliardi et al 2023, Leroy et al 2023) variation in root morphological traits that are found here to predict the community composition of the root‐associated microbiome.…”
Section: Extending the Root System: Incorporating Microbial Communiti...mentioning
confidence: 59%
See 4 more Smart Citations
“…In contrast, Merino‐Martín and collaborators (2023) only observed differences in fungal, but not bacterial communities, between rhizosphere and bulk soil along an elevation gradient. This rhizosphere effect is also partly related to variation in inter‐ (Mafa‐Attoye et al 2023, Merino‐Martín et al 2023) and intraspecific (Gagliardi et al 2023, Leroy et al 2023) variation in root morphological traits that are found here to predict the community composition of the root‐associated microbiome.…”
Section: Extending the Root System: Incorporating Microbial Communiti...mentioning
confidence: 59%
“…1) may appear to shift along the collaboration axis but this may not reflect a shift in the species' dependency on mycorrhizal fungi. Similarly, root traits may change with plant ontogeny, changing from thin to thick roots as plants grow bigger (Leroy et al 2023) (Species 2; Fig. 1).…”
Section: Intraspecific Patterns In Root Trait Variation: Insights Tow...mentioning
confidence: 99%
See 3 more Smart Citations